Requirements for Volunteers' Participation in Sports - Seyed Emad Hosseini; AmirReza Khadem; Maryam SoleymaniThehrani; Maziyar Kalashi; Mohammad Pourkiani (Archives in Sport Management and Leadership)
This research was carried out with the aim of the requirements for the participation of volunteers in sports. The research method was a descriptive survey and applied in terms of purpose. The statistical population of the research was the officials of sports and youth departments of Isfahan province (experts, managers, presidents) and some sports committees of Isfahan province. The random sampling method was simple and 129 people were selected as a statistical sample. The research tool was a questionnaire. The overall reliability of the questionnaire was also obtained using Cronbach's alpha test (0.988). This research used a structural equation model to analyze the data using PLS version 3 software. The research findings showed that management requirements have a positive and significant effect on the participation of volunteers in sports and its effectiveness is 0.978. Social requirements have a positive and significant effect on the participation of volunteers in sports, and its effectiveness is 0.915. Individual requirements have a positive and significant effect on the participation of volunteers in sports, and its effectiveness is 0.829. Also, cultural requirements have a positive and significant effect on the participation of volunteers in sports, and its effectiveness is 0.917. Based on the findings of this research, we conclude that to develop the state of participation of volunteers in sports, it is necessary to focus on the categories extracted from this research, and based on this, platforms for the participation of sports volunteers should be created according to different requirements.